Seeking a life partner with the use of internet technology - Rychłowska-Niesporek, Agnieszka (Uniwersyteckie Czasopismo Socjologiczne, 2019)
Since its beginning Internet has been used for matrimonial purposes. The first dating portals were launched in the United States already in the first half of the 1990s. The research shows that the number of people searching for partners and spouses via the Internet has been constantly growing. Searching for a life partner using online tools is also connected with the development of new strategies. The paper presents the results of a study conducted among singles . The research involved a qualitative study conducted among singles in the Silesian region and a nation-wide quantitative online study among the singles using sympatia.pl – one of the popular dating portal in Poland. The research findings show the interest of singles in searching for life partners on the Internet, but also their scepticism about the possibility of finding a valuable life partner in this way.